2018
DOI: 10.14218/jcth.2018.00035
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury at Admission Is a Better Predictor of Mortality than Its Persistence at 48 h in Patients with Acute-on-chronic Liver Failure

Abstract: Background and Aims: Acute kidney injury (AKI) occurs commonly in patients with acute-on-chronic liver failure (ACLF). However, there are scant data regarding the impact of AKI on survival in ACLF. We performed a prospective study to evaluate the impact of AKI on survival in ACLF.Methods: This study was conducted in ACLF patients hospitalized in the Gastroenterology Department of Sriram Chandra Bhanja Medical College (India) between October 2016 and February 2018. Demographic, clinical and laboratory parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The current study developed a novel online individual mortality risk predictive tool based on an RSF algorithm [35,36] age, [35,37,38] INR, [4,36,38,39] RDW, [40,41] AKI, [42][43][44] and serum sodium level. [45,46] The RSF algorithm could identify the variables that had a nonlinear effect on prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The current study developed a novel online individual mortality risk predictive tool based on an RSF algorithm [35,36] age, [35,37,38] INR, [4,36,38,39] RDW, [40,41] AKI, [42][43][44] and serum sodium level. [45,46] The RSF algorithm could identify the variables that had a nonlinear effect on prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Organ failures, especially AKI, form the diagnostic criteria for ACLF according to the European Association for the Study of the Liver (EASL) definition 1 . Furthermore, the presence of AKI determines the outcome of patients with ACLF 2 4 . The cause of AKI in ACLF is multi-factorial 3 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 31 ] found that the proportion of patients with HRS-AKI was 3/20 in children and 22/380 in ACLF according to the EASL/CLIF criteria. However, some studies in the Asia-Pacific region have reported the epidemiologic data of HRS-AKI according to the APASL or CMA criteria ( Table 5 ) [ 14 , 24 , 32–38 ].…”
Section: Epidemiology Of Hrs In Aclfmentioning
confidence: 99%